EU 4.0 - The debate on digitalisation and the labour market in Europe - Karen Grass; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
In the recent years an intensive discussion in politics, research, business and society on the influence of digitalisation on the working world has evolved. This development is expected to exert profound effects on the use of human labour. However, judgements widely diverge. The comprehensive debates on "industry 4.0" and "labour 4.0" in Germany are concerned with influences of digitalisation on the economy and the labour market, substitutability of jobs as well as conditions, qualifications and regulations for a new world of employment. Thereby, the discussions are characterised by large uncertainty regarding the future development and thus often focus more on exploration rather than on confronting firmly established positions. This in particular makes it valuable to feed additional information into the national debates. In this, it is worth looking into other countries: Which is the stance of digitalisation, how is the influence on the working world evaluated? Which political positions and measures are discussed? Which programmes and projects were established, are results already conceivable? The underlying report gives an overview for several European countries and for the level of the European Union. Regarding digitalisation, it considers the areas of economic developments, tasks and competences as well as working conditions and changes of the world of employment. – – In den vergangenen Jahren ist eine intensive Diskussion in Politik, Wissenschaft, Wirtschaft und Gesellschaft um die Wirkungen der Digitalisierung auf die Arbeitswelt entstanden. Von dieser Entwicklung wird ein teils tiefgreifender Einfluss auf den Einsatz menschlicher Arbeit erwartet. Allerdings gehen die Einschätzungen dabei weit auseinander. In den umfassenden Debatten zu "Industrie 4.0" und "Arbeit 4.0" in Deutschland geht es vor allem um Auswirkungen der Digitalisierung auf Wirtschaft und Arbeitsmarkt, Substituierbarkeit von Jobs sowie Bedingungen, Qualifikationen und Regulierungen für eine neue Arbeitswelt. Dabei ist die Diskussion vielfach von noch großen Unsicherheiten über die weitere Entwicklung geprägt und hat dementsprechend in Teilen auch den Charakter des Erkundens statt nur eines Abgleichs festgefügter Positionen. Gerade das lässt es wertvoll erscheinen, zusätzliche Informationen und Ideen in die nationalen Debatten einzubringen. So lohnt sich ein Blick in andere Länder: Wie ist hier der Stand der Digitalisierung, wie wird die Betroffenheit der Arbeitswelt eingeschätzt? Welche politischen Positionen und Maßnahmen sind in der Diskussion? Welche Programme und Projekte wurden etabliert, sind bereits Ergebnisse sichtbar? Dieser Bericht gibt dazu einen Überblick für verschiedene europäische Staaten sowie die Ebene der Europäischen Union. Inhaltlich werden im Hinblick auf die Digitalisierung die Bereiche wirtschaftliche Entwicklungen, Tätigkeiten und Kompetenzen sowie Arbeitsbedingungen und Änderungen der Arbeitswelt betrachtet.
Keywords: J20; O33; 330; Digitalisation; European Union; Labor market